Design report on the manufacture of iron oxide, red lead and litharge and white lead - Montelibano, Donnie A. (College of Engineering, 1961)
It has been shown that the oxidation processes for litharge and red lead, the carter process for white lead and the calcination of copperas for iron oxide are practical processes applicable and desired in the Philippines. At a capacity of 2 tons litharge, 2 tons white lead, 5 tons red lead, 5 tons iron oxide on a daily basis, a capital investment of P4,296,079.13 and a working capital of P888,642.00 is needed. Annual sales is P4,920,000.00 Net profit is P507,508,49 and the percentage return on investment is 11.82 percent. The plant site is in Marikina bordered by the river on one side. The land area is 27,800 square meters. Capital investment can be recovered in eight (8) years after attaining full capacity and if no dividends are paid out in these years.